2023
DOI: 10.3390/su15053910
|View full text |Cite
|
Sign up to set email alerts
|

Income Inequality, Household Debt, and Consumption Growth in the United States

Abstract: In this paper, the SV-TVP-VAR model is used to study the relationships between income inequality, household debt, and consumption growth in the US. This is of great significance for studying whether household debt can become a “substitute” for income and whether it is possible to achieve sustainable growth in consumption under the background of worsening income inequality. According to the research results, the main conclusions are as follows: Firstly, the widening of income inequality would increase consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Contrary to the conclusions of Bai et al (2023) found that income disparity is positively and in most cases strongly connected with economic growth. Using a more comprehensive data set on income inequality, Ali (2023) and Piao et al (2023) revaluated the association between income disparity and economic growth and found a robust positive correlation between an increase in income inequality and subsequent economic growth in the short and medium term. Peña Proaño, and Schnellbacher ( 2023) used a cross-country analysis of the impact of income inequality on economic growth in India and found that inequality actually had a large, positive impact on state economies.…”
Section: Found Evidence Of a Positive Correlation Between Income Ineq...mentioning
confidence: 99%
“…Contrary to the conclusions of Bai et al (2023) found that income disparity is positively and in most cases strongly connected with economic growth. Using a more comprehensive data set on income inequality, Ali (2023) and Piao et al (2023) revaluated the association between income disparity and economic growth and found a robust positive correlation between an increase in income inequality and subsequent economic growth in the short and medium term. Peña Proaño, and Schnellbacher ( 2023) used a cross-country analysis of the impact of income inequality on economic growth in India and found that inequality actually had a large, positive impact on state economies.…”
Section: Found Evidence Of a Positive Correlation Between Income Ineq...mentioning
confidence: 99%
“…The rapid rise of household debt significantly impacts consumption (Piao et al, 2023;Yan & Zhu, 2013). In the short term, financial institutions provide loans in a timely and effective manner with lower costs and relaxed conditions that promote current consumption (Xiong, 2014).…”
Section: Theoretical Basis and Hypotheses Developmentmentioning
confidence: 99%
“…China has a dual social structure comprised of urban and rural areas. There are significant differences between urban and rural families regarding income level, assets, and culture (Piao et al, 2023). Urban families have a higher income level, and their social security level is more stable than rural families.…”
Section: Theoretical Basis and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations